Die houding van jeuglede teenoor die Christian Youth Movement : die rol van 'sense of coherence' - Links, A. G.(Aldrin Godfrey) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1999.